Dopaminergic modulation of propofol-induced activation in VLPO neurons: the role of D1 receptors in sleep-promoting neural circuits - Kun Qian; Kun Qian; Yu Zhang; Yang Liu; Sisi Wu; Zikun Duan; Jianhao Liao; Jianhao Liao; Wei Luo; Mo Zhou; Xuejiao Dou; Xingkui Liu; et al. (Frontiers in Neuroscience)
BackgroundThe ventrolateral preoptic nucleus (VLPO) is a crucial regulator of sleep, and its neurons are implicated in both sleep-wake regulation and anesthesia-induced loss of consciousness. Propofol (PRO), a widely used intravenous anesthetic, modulates the activity of VLPO neurons, but the underlying mechanisms, particularly the role of dopaminergic receptors, remain unclear.ObjectiveThis study aimed to investigate the effects of PRO on NA (−) neurons in the VLPO and to determine the involvement of D1 and D2 dopaminergic receptors in mediating these effects.MethodsUsing in vitro patch-clamp techniques, we identified and characterized NA (−) and NA (+) neurons in the VLPO based on their morphological, pharmacological, and electrophysiological properties. We assessed the effects of PRO on spontaneous excitatory postsynaptic currents (sEPSCs) and inhibitory postsynaptic currents (sIPSCs) in NA (−) neurons, both in the presence and absence of dopaminergic receptor modulators.ResultsPRO significantly increased the firing frequency of NA (−) neurons while decreasing the firing frequency of NA (+) neurons. This activation of NA (−) neurons was mediated through GABA_A receptors, as evidenced by the increased frequency of sEPSCs and altered sIPSCs dynamics. Dopamine (DA) attenuated the PRO-induced increase in sEPSCs frequency and suppression of sIPSCs frequency in NA (−) neurons via D1 receptors, but not D2 receptors. Blocking D1 receptors with SCH23390 reversed the effects of DA on PRO-induced changes, while D2 receptor antagonist sulpiride had minimal impact.ConclusionOur findings demonstrate that PRO excites sleep-promoting NA (−) neurons in the VLPO, primarily through GABA_A receptors, with dopaminergic modulation occurring via D1 receptors. These results provide new insights into the neural mechanisms underlying general anesthesia and highlight the potential role of dopaminergic signaling in modulating anesthetic effects on sleep-related neural circuits.